Juvenile delinquency and conformism - Eleonora Patacchini; Yves Zenou (Fondazione Eni Enrico Mattei (FEEM), 2010)
This paper studies whether conformism behavior affects individual outcomes in crime. We present a social network model of peer effects with ex-ante heterogeneous agents and show how conformism and deterrence affect criminal activities. We then bring the model to the data by using a very detailed dataset of adolescent friendship networks. A novel social network-based empirical strategy allows us to identify peer effects for different types of crimes. We find that conformity plays an important role for all crimes, especially for petty crimes. This suggests that, for juvenile crime, an effective policy should not only be measured by the possible crime reduction it implies but also by the group interactions it engenders.
Keywords: A14; C21; D85; K42; Z13; 330; Social Networks; Linear-in-means Model; Spatial Autoregressive Model; Social Norms